Ts. Dr. Mohd Izham develops Track Me app with geofence to monitor childrens movement - Nur Hartini, Mohd Hatta (2022)
PEKAN, 30 June 2022 – Cases of child loss worldwide and in Malaysia particularly are not new. In fact, these disappearances often also end in murder or serious abuse.